Investigation morphological, electrical, and optical properties of Mn-doped ZnO thin film by sol-gel spin-coating method - Cavas, Mehmet (Springer Heidelberg, 2017)
In this study, ZnO was doped with 0.01% Mn and it is grown on p-Si by the sol-gel spin-coating method. Obtained the thin film was studied that to understand the effect of 0.01% Mn-doping ratio on the optical and electrical properties of ZnO structure. In this context, first, the morphological structure of the thin film was studied with the use of atomic force microscopy (AFM). The surface structure was obtained homogeneous, and roughness and fiber size were calculated between 27.2-33.6 and 0.595-0.673 nm, respectively. Second, the optical properties were characterized via ultraviolet-visible (UV-Vis) spectrophotometry. Third, the effect of light intensity on junction properties of the photodiode was studied. The current-voltage (I-V) of the photodiode was measured under dark and at the different intensities of illumination. Obtained results showed that the current of photodiode was increased with the intensity of illumination from 6.41 x 10(-7) to 5.32 x 10(-4) A. These results indicate that photocurrent under illumination is higher than the dark current. After that, the other parameters of the photodiode such as barrier height and ideality factor were determined from forwarding I-V plots using the thermionic emission model that the barrier height and the ideality factor were found 0.74 eV and 5.3, respectively. On the other hand, the capacitance-voltage (C-V) was measured at the different frequencies. The C-V characteristic shown that C-V characteristic of the photodiode was changed depends on increasing frequency. In addition, the interface density (D (it)) value was decreased by increasing frequency too. Similarly, the serial resistance of the photodiode was also decreased by increasing frequency. Received all these results indicated that Mn-doped ZnO thin film sensitive to light and due to this property, it can be used for different optoelectronic applications as a photodiode and photosensor.
Keywords: Optical sensor; Photodiode; Nanomaterials; Thin film; ZnO film